Gastric Adenocarcinoma: A Multimodal Approach - Quadri, Humair S.; Smaglo, Brandon G.; Morales, Shannon J.; Phillips, Anna Chloe; Martin, Aimee D.; Chalhoub, Walid M.; Haddad, Nadim G.; Unger, Keith R.; Levy, Angela D.; Al-Refaie, Waddah B. (Frontiers in Surgery, 2017)
Despite its declining incidence, gastric cancer remains a leading cause of cancer-related deaths worldwide. A multimodal approach to gastric cancer is critical to ensure optimal patient outcomes. Pre-therapy fine resolution contrast-enhanced cross-sectional imaging, endoscopic ultrasound and staging laparoscopy play an important role in patients with newly diagnosed ostensibly operable gastric cancer to avoid unnecessary non-therapeutic laparotomies. Currently, margin negative gastrectomy and adequate lymphadenectomy performed at high volume hospitals remain the backbone of gastric cancer treatment. Importantly, adequate gastric cancer surgery should be integrated in the setting of a multimodal treatment approach. Treatment for advanced gastric cancer continues to expand with the emergence of additional lines of systemic and targeted therapies.